2007
DOI: 10.1039/b617782b
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth in nanoporous framework materials

Abstract: Future applications of nanoporous materials will be in opto-electronic devices, magnetic and chemical sensors, shape-selective and bio-catalysis, structural materials and nuclear waste management. Crucially, in all such applications, an understanding of crystal growth to the same depth as has been achieved in semiconductor technology is needed. Therefore, defects, intergrowths, dopants and isomorphous substitution must be controlled, and crystal habit and size (e.g. single crystal films) must be fabricated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The implementation of instrumental techniques, apparent in Faraday Discussion 95, has been a very strong feature of Discussion 136, with an unprecedented variety in evidence and a trend towards multi-technique studies. [16][17][18] Strikingly, the techniques have addressed the solution as much as, if not more than, the surface, and the importance of solution entities and precursors in determining the outcome of crystallisation has been an important theme. This aspect has been seen in studies of molecular materials, 16,19 where spectroscopic techniques have afforded detailed information on molecular interactions in solution.…”
Section: From Surfaces To Solutionsmentioning
confidence: 99%
“…The implementation of instrumental techniques, apparent in Faraday Discussion 95, has been a very strong feature of Discussion 136, with an unprecedented variety in evidence and a trend towards multi-technique studies. [16][17][18] Strikingly, the techniques have addressed the solution as much as, if not more than, the surface, and the importance of solution entities and precursors in determining the outcome of crystallisation has been an important theme. This aspect has been seen in studies of molecular materials, 16,19 where spectroscopic techniques have afforded detailed information on molecular interactions in solution.…”
Section: From Surfaces To Solutionsmentioning
confidence: 99%
“…99 Additionally, Piana et al have developed a kinetic Monte Carlo scheme and have applied it to the growth of urea crystals from water. 100 A similar scheme was followed by Anderson et al 101 to predict the shape of hydrothermally synthesized zeolite A crystals. These simulation techniques have both advantages and drawbacks compared to the modeling methods described in §5.1 for problems ranging from fundamental discovery to product and process development.…”
Section: Crystal Simulationsmentioning
confidence: 99%
“…Interestingly, zeolite A crystals 15 showed similar etch pits but since these crystals were never investigated by in situ methods it is unknown whether these are also spiral dissolution pits. In situ AFM revealed that these etch pits are tight spiral dissolution pits.…”
mentioning
confidence: 99%
“…This is an unusual phenomenon and to our knowledge never reported previously. Interestingly, zeolite A crystals 15 showed similar etch pits but since these crystals were never investigated by in situ methods it is unknown whether these are also spiral dissolution pits. Monte Carlo simulations show that during dissolution conditions spiral dissolution pits can be generated.…”
mentioning
confidence: 99%